In-vitro and in-vivo evaluation of modified sodium starch glycolate for exploring its haemostatic potential. (1st May 2020) - Panwar, Vineeta; Thomas, Jijo; Sharma, Anjana; Chopra, Vianni; Kaushik, Swati; Kumar, Ashutosh; Ghosh, Deepa
Highlights: Hemostatic potential of Sodium starch glycolate (SSG) and porous SSG (pSSG) was studied. The biodegradability and biocompatibility of SSG and pSSG were comparable. In comparison to starch and SSG, pSSG had higher fluid uptake capacity. In-vitro, pSSG displayed improved platelet activation and clot formation. The ability to stop blood loss in rats was significant in pSSG in comparison to SSG. Abstract: The control of blood flow from breached blood vessels during surgery or trauma is challenging. With the existing treatment options being either expensive or ineffective, the development of a haemostat that overcome such drawbacks would be beneficial. With an aim to develop an ideal haemostat, the potential of sodium starch glycolate (SSG), a commonly used pharmaceutical disintegrant was modified to obtain porous microparticles (pSSG). The biodegradability, cyto-compatibility and haemo-compatibility of the modified particles were confirmed using appropriate studies. In comparison to starch and SSG, the irregular shaped pSSG demonstrated spontaneous and significant fluid absorption (3500+ 500 %) and formed a physical barrier to blood flow. In addition, significant blood cells aggregation and platelet activation was observed in the modified micoparticles leading to rapid clot formation. In-vivo studies on liver and abdominal artery injury models in rats indicated the superior haemostatic potential of pSSG over SSG and starch. The results indicated that pSSG can be explored further in clinical evaluation as a hemostat.